2020
DOI: 10.1007/s40121-020-00347-w
|View full text |Cite
|
Sign up to set email alerts
|

Financial Analysis of Dalbavancin for Acute Bacterial Skin and Skin Structure Infections for Self-Pay Patients

Abstract: Introduction Acute bacterial skin and skin structure infections (ABSSSI) are an increasing cause of admission in the self-pay population. We previously reported that patients with ABSSSI discharged to receive dalbavancin showed a decreased length of stay (LOS) and total direct costs without increasing 30-day readmission rate. For patients who are financially eligible, a dalbavancin vial replacement program can offset costs. The objective of this study was to determine cost differences in treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In addition, the majority of patients in this study were uninsured with limited or no consistent source of income. Of note, reimbursement for LaLGPs varies based on site of administration (i.e., inpatient versus outpatient) [ 9 ]. A stewardship-led initiative at our institution to assist in transitions of care for patients receiving LaLGPs includes the proactive use of a patient assistance program (PAP) available from the manufacturer (AbbVie Inc. ® , North Chicago, IL, USA), where medication vials may be sent directly from the company at no cost for qualifying patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the majority of patients in this study were uninsured with limited or no consistent source of income. Of note, reimbursement for LaLGPs varies based on site of administration (i.e., inpatient versus outpatient) [ 9 ]. A stewardship-led initiative at our institution to assist in transitions of care for patients receiving LaLGPs includes the proactive use of a patient assistance program (PAP) available from the manufacturer (AbbVie Inc. ® , North Chicago, IL, USA), where medication vials may be sent directly from the company at no cost for qualifying patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data examining clinical outcomes and cost savings in patients with osteomyelitis and infective endocarditis who received LaLGPs [ 5 , 6 , 7 , 8 , 9 ]. Although these data are encouraging, the studies are often descriptive in nature, limited to a single hospital, or focused on ABSSSI as an indication.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, potential health risks associated with prolonged hospitalization should be taken into account, as well as the improvement in the quality of life related to early discharge. Beyond the hospital perspective, a small study also suggested decreased direct and indirect costs for self-pay (i.e., uninsured, usually with a low income) patients with ABSSSIs who were switched to dalbavancin after discharge [18].…”
Section: Discussionmentioning
confidence: 99%
“…Most economic studies have extrapolated the reduction in the LoS observed in real-life studies compared to usual treatments to a reduction in hospitalization-related costs from a societal perspective [15][16][17]. A budget impact analysis of dalbavancin use in a small series of twelve self-pay patients treated for ABSSSIs [18] was carried out, but its specific context (self-pay patients in the USA) made it hardly extrapolatable. To date, no comparison between dalbavancin and standard of care in real patients has been carried out with an economic analysis on the impact on the LoS.…”
Section: Introductionmentioning
confidence: 99%
“…Several other reports position DAL as a cost-saving alternative [55,56], although, in a recent study, the results of González et al pointed in the opposite direction [57], finding DAL to be more expensive than the standard of care for the treatment of skin and soft tissue infections. Nevertheless, in the same journal, Bookstaver et al replied with more specific considerations other than cost and calling for other issues to be taken into account when thinking about antimicrobial stewardship [58].…”
Section: Dal As a Cost-saving Strategymentioning
confidence: 94%